Clostridium difficile Infection of a Total Hip Arthroplasty: Case Report and Review of the Literature. Issue 1 (January 2020) - Loloi, Justin; Mrowczynski, Oliver; Claxton, Benjamin; Abdulbasit, Muhammad; Schade, Meredith
Abstract : Case: We describe the case of an 85-year-old woman who presented with worsening right hip pain after a conversion hip replacement. Subsequent imaging demonstrated a gas-containing collection in the lateral thigh. She was taken to the operating room for irrigation and debridement, where intraoperative cultures returned positive for Clostridium difficile. Surgical management was followed by a prolonged course of antibiotics. Conclusions: Clostridium difficile as the etiology of infection in a conversion arthroplasty is exceedingly rare. Orthopaedic surgeons and infectious disease specialists should consider C. diff as a potential cause of infection in conversion hip arthroplasty because management options will need to be tailored.